Analisis Tren Penjualan dan Dinamika Pasar: Studi Kasus PT. Enseval Putera Megatrading - daud tri bakti purba (Jurnal Riset Informatika dan Teknologi Informasi, 2025)
This study aims to analyze the sales trends and market dynamics of PT. Enseval Putera Megatrading over a specific period. The data used includes sales information from various branches across Indonesia, obtained from monthly and annual sales reports. Through this analysis, we identified consistent and fluctuating sales patterns, as well as the factors influencing sales, both internally, such as marketing strategies, service quality, and inventory management, and externally, such as economic conditions, market competition, and government policy changes. This research also measures the effectiveness of various sales strategies implemented by the company, with the aim of providing data-driven recommendations to enhance future sales performance. The results of the study show significant sales variations between branches and periods, caused by several internal factors like sales team performance and external factors such as market demand trends and raw material price fluctuations. These findings offer valuable insights for management in formulating more effective and adaptive strategies in response to the ever-changing market dynamics.